Knowledge and prevalence of post-menopausal health problems among women attending a tertiary care hospital in Ajman: cross-sectional study - Ketranji, Omar; Al-Mubarak, Abdullah Nameer Ali; Mohammad, Ibrahim; Khokar, Sara; YAlhenshiri, Abdulmonaem Mohamed; Sreejith, Anusha (International Journal Of Community Medicine And Public Health, 2020)
Background: Many physiological and psychological changes happens to women during the time of menopause. The symptoms differ according to the individual, culture and ethnicity. As the women pass through various stages of menopause, the prevalence of symptoms also varies. This study aimed to assess the knowledge of post-menopausal health problems among the women above 45 years old and to identify the prevalence of symptoms in post-menopausal life. Methods: A cross-sectional study was conducted in a private hospital in Ajman, UAE among women aged 45 years and above with a validated self-administered questionnaire. Ethics approval was obtained before the study. Data were coded, entered, and analyzed using SPSS version 24. Chi-square tests and descriptive statistics like frequency tables and crosstabs were used. Results: The mean age of women participants was 50.7 years. The results showed that 50.2% of the women had moderate knowledge about post-menopausal health problems, while 37% and 12.8% had excellent and poor knowledge, respectively. Prevalence of post-menopausal symptoms among women were hot flushes (55.1%), dry skin (54.7%), muscle pain (54.5%), joint pain (52.9%), and weight gain (51%). Women suffered from at least one of the post-menopausal symptoms. Hot flushes, dry skin, muscle pain, and weight gain were significantly associated with the menopausal status (p<0.05). Conclusions: Post-menopausal symptoms hot flushes, dry skin, and muscle pain were significantly associated with a peri-menopausal or post-menopausal state. Women must be made aware of these symptoms and their causes and treatments as well.